Der Runen-Stein von Rök und Snorri Sturluson - oder 'Wie aussagekräftig sind unsere Quellen zur Religionsgeschichte der Wikingerzeit?' - Meulengracht Sørensen, Preben (Scripta Instituti Donneriani Aboensis, 1990)
The article contributes to the discussion on source criticism within the research field of Old Norse religion. It examines the common assumption that archaeological sources are always to prefer above written sources from the Middle Ages where the Viking Era is described as such accounts are invariably tendentious and biased. Influenced by theories from the field of social anthropology, however, the article argues for the worth of written sources as a complement to the material ones. As an example, the effort to interpret the inscriptions on the runic stone from Rök are introduced. The article suggests that different kinds of source material offer a spectrum of possibilities out of which none alone, but rather all taken together, can deepen the researcher’s knowledge about the object under study.